Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Tuberkulosis Paru Di Ruang Paru Rsud Prof. H. Muhammad Yamin,Sh - Anggun Fitriani; Hilma Yessi; Debby Silvia Dewi; Mike Asmaria (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Pulmonary tuberculosis (TB) is a contagious infectious disease that remains a global and national health problem. It is caused by Mycobacterium tuberculosis and is transmitted through droplets. Based on data from the World Health Organization (WHO) in 2024,the number of TB cases reached approximately 10.7 million worldwide.In Indonesia, there were around 889,000 cases,while in West Sumatra Province there were approximately 25,000 tuberculosis cases. At RSUD Prof. H. Muhammad Yamin, S.H. Pariaman,the number of cases in the last three years was 56 cases in 2023, 69 cases in 2024, and 45 cases in 2025.The purpose of this case study is to provide nursing care for a pulmonary TB patient in the pulmonary inpatient ward at RSUD Prof. H.Muhammad Yamin, S.H. The method used is a case study with a duration of 5 days,conducted from February 5 to February 9, 2026, in the pulmonary ward of RSUD Prof. H.Muhammad Yamin,S.H.Pariaman.The approach used is the nursing process,which includes assessment,diagnosis, intervention,implementation, and evaluation stages,with one patient diagnosed with pulmonary TB as the subject.The results identified six nursing diagnoses: ineffective airway clearance,hyperthermia,disturbed sleep pattern,risk of nutritional deficit,risk of infection,and knowledge deficit.The nursing interventions provided included airway management,hyperthermia management,sleep support,nutritional management,infection prevention,and health education.The evaluation over five days showed that all nursing problems were resolved,and the patient was allowed to be discharged.Patients and their families are expected to adhere to the full course of treatment,adopt a healthy lifestyle, use masks, and increase the intake of nutritious food to support recovery and prevent transmission.